If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + 3)(6x + -8) = 0 Reorder the terms: (3 + 5x)(6x + -8) = 0 Reorder the terms: (3 + 5x)(-8 + 6x) = 0 Multiply (3 + 5x) * (-8 + 6x) (3(-8 + 6x) + 5x * (-8 + 6x)) = 0 ((-8 * 3 + 6x * 3) + 5x * (-8 + 6x)) = 0 ((-24 + 18x) + 5x * (-8 + 6x)) = 0 (-24 + 18x + (-8 * 5x + 6x * 5x)) = 0 (-24 + 18x + (-40x + 30x2)) = 0 Combine like terms: 18x + -40x = -22x (-24 + -22x + 30x2) = 0 Solving -24 + -22x + 30x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(-12 + -11x + 15x2) = 0 Factor a trinomial. 2((-3 + -5x)(4 + -3x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-3 + -5x)' equal to zero and attempt to solve: Simplifying -3 + -5x = 0 Solving -3 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -5x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -5x = 0 + 3 -5x = 0 + 3 Combine like terms: 0 + 3 = 3 -5x = 3 Divide each side by '-5'. x = -0.6 Simplifying x = -0.6Subproblem 2
Set the factor '(4 + -3x)' equal to zero and attempt to solve: Simplifying 4 + -3x = 0 Solving 4 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -3x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -3x = 0 + -4 -3x = 0 + -4 Combine like terms: 0 + -4 = -4 -3x = -4 Divide each side by '-3'. x = 1.333333333 Simplifying x = 1.333333333Solution
x = {-0.6, 1.333333333}
| x^2-16x-4=0 | | 9x^2-1.4x+0.6=0 | | -13-4=9 | | (10x-6)(5x+4)= | | 9x^2-1.4+0.6=0 | | 5x*x-8x=0 | | -9x^0=0 | | 12a+7=7a+2 | | 3(5x-3)-10=-34 | | 49=26-8(3-5w) | | 8.833x^2-1.422x+0.5842=0 | | (2a+7)(4a+10)= | | 10x-5-4x-3+2=0 | | -6=3(3x-5) | | 7x+4=45 | | -12=2(5x-1) | | 21x+15=15 | | -w-2=42 | | 0=x^2+6x-8 | | 6a+2=-a+30 | | (xy)(x^2y)(x^2y)(x^2y)(x^2y)=0 | | 1x+4y=168 | | 21x+5=15 | | x^2-4x-37=0 | | 3x^2+9x-2=-4 | | (xy)(x^2y)(xy)(x^2y)(xy)(x^2y)(xy)(x^2y)=0 | | 3x-5x=8-9 | | log*5(-6-2x)=2 | | (x^2D^2-4xD+6I)y=C | | (xy)(x^2y)(xy)(x^2y)(xy)(x^2y)=0 | | 15y+4=24 | | (5y+6)-(3y+4y)=10 |